The Origins of Tropical Rainforest Hyperdiversity. (November 2015) - Pennington, R. Toby; Hughes, Mark; Moonlight, Peter W.
Abstract : Traditional models for tropical species richness contrast rainforests as 'museums' of old species or 'cradles' of recent speciation. High plant species diversity in rainforests may be more likely to reflect high episodic evolutionary turnover of species–a scenario implicating high rates of both speciation and extinction through geological time.